Requirements Engineering: Foundation for Software Quality: 19th International Working Conference, REFSQ 2013, Essen, Germany, April 8-11, 2013. Proceedings - Dörr, Jörg; Opdahl, Andreas L. (Lecture notes in computer science, 2013)
This book constitutes the refereed proceedings of the 19th International Working Conference on Requirements Engineering: Foundation for Software Quality, REFSQ 2013, held in Essen, Germany, in April 2013. The papers are organized in 8 topical sections on requirements engineering and architecture; natural language requirements; requirements engineering and quality; traceability; requirements engineering and business/goals; requirements engineering and software development; requirements engineering in practice; product lines and product management
Literaturangaben
Keywords: Konferenzschrift -- 2013 -- Essen; Konferenzschrift; Qualitätssicherung; Softwareprodukt; Requirements engineering